DESIGN OF SEWING MACHINE OPERATOR AIDS USING THE QUALITY FUNCTION DEPLOYMENT (QFD) METHOD AT DEANISA CONVECTION - Kartika Napu; Eduart Wolok; Idham Halid Lahay (Jurnal Ilmu Teknik Terapan, 2025)
The convection industry in Indonesia faces challenges in improving eﬃciency and productivity, especially in the work process of sewing machine operators. This research aims to design tools that can improve operator performance using the Quality Function Deployment (QFD) method. The QFD method was chosen because of its ability to identify and translate user needs into appropriate design specifications. Deanisa Sport Convection is a business engaged in the production of clothing, including oﬃce uniforms, school uniforms, alma mater jackets, and training sets. From the results of preliminary observations in the field, defective products produced from convection are still quite a lot in the period 2023 to 2024. There are many products that experience defects including errors in the sewing process. The data obtained is then analyzed and mapped into a QFD matrix, which connects user needs with the technical characteristics of the tools to be designed. The final design of the resulting tool is expected to increase operator comfort and productivity, and reduce product defects during the production process. By using the QFD method in designing assistive devices for sewing machine operators, it can produce product designs that meet the needs of sewing operators and have optimal features.